Evaluation of Subdistrict Tasks in Implementation the Authority for Small-Scale Development in Kutai Kartanegara Regency - Muhammad Subandi; Ince Raden; Heru Suprapto (Institut Pemerintahan Dalam Negeri, 2021)
The implementation of sub-district tasks in managing small-scale development, which is the delegation of authority from the Regent of Kutai Kartanegara, has not been running optimally. This study aims to evaluate the authority of the sub-district in implementing small-scale development. The research method is descriptive qualitative by collecting data through semi-structured interviews conducted in 3 sub-districts and using a questionnaire for all locations in 15 sub-districts which are the source of the data. with the determination of informants by purposive sampling. From the results of the study, it has been concluded that the sub-district's authority in managing small-scale development cannot be fully implemented, this is due to the lack of clarity in the provisions regarding the criteria and specifications for an activity in the delegation of authority regulations, the weak coordination link between the sub-districts and the relevant local government agencies in the framework of the integrated planning system, lack of capacity sub-district officials in carrying out their duties, there is no measurable sub-district performance indicators and targets, it is recommended to the Kutai Kartanegara Regency Government to review to make improvements and development of policies regarding the delegation of the Regent's authority to the Camat, especially related to small-scale management policies and adjusting to the prevailing laws and regulations governing regional and sub-district governments.